Music Worlds and Internal Goods: The Role of Convention. (March 2015) - Crossley, Nick; Bottero, Wendy
What is the basis of the value and pleasure that participants derive from participation in music worlds? Participants often have a great passion for those worlds and for the artists, works, identities and conventions which constitute and populate them. Sociology, however, is not very good at explaining or exploring such passion and commitment. To do this in relation to music requires that we take the pleasures and satisfactions of 'musicking' (i.e. all activities pertaining to music) seriously. This paper calls for an interrogation of the mechanisms and dynamics of music's intrinsic pleasures. We argue that it is necessary to explore the mechanisms involved in the intrinsic pleasures of musicking, and that to do so means analysing the 'internal goods' of music worlds and the role that conventions play in the production of pleasure and commitment.